The effect of horticultural activity program on internet addiction, social skills, and stress levels in children: A randomized controlled trial. - Kacar, Dilek; Ayaz-Alkaya, Sultan (Journal of Pediatric Nursing, 2026)
Internet addiction is a growing problem among children and adolescents. Pathological internet use may lead to psychological and social issues. More effective and innovative interventions are needed to promote the mental health of children. This study aimed to investigate the effects of a horticultural activity program on internet addiction, social skills, and perceived stress in children. A parallel-group randomized controlled trial was adopted. A total of 60 children (aged 11–12 years) were recruited and randomly assigned to either the experimental group (n = 30) or the control group (n = 30). Data were collected using validated instruments, including the Personal Information Form, the Internet Addiction Scale for Adolescents, the Perceived Stress Scale for Children, the Social Skills Scale, and the Social Skills Evaluation Scale. The experimental group participated in a six-week Horticultural Activity Program. The data were analyzed using the Chi-square test for categorical variables and a mixed-design (two-way repeated-measures ANOVA) with Bonferroni Comparison Test. At post-test, and at both the first (3rd month) and second (6th month) follow-up measurements, children in the experimental group demonstrated significantly lower mean scores for internet addiction and significantly higher mean scores for social skills compared to the control group (p < 0.05). The intervention revealed large effect sizes, with partial eta squared values of 0.270, 0.301, and 0.337, respectively. After the intervention, no significant group-by-time interaction was found between the experimental and control groups (p = 0.159) regarding the mean scores of perceived stress. The present study concluded that the horticultural activity program was effective in reducing internet addiction and enhancing social skills in children. However, no significant effect was observed on perceived stress levels. Nurses could perform a horticultural activity program to prevent addictive behaviors among children. Nurses could encourage parents to participate in horticultural activities as a meaningful and constructive leisure activity. • Internet addiction is an increasingly significant problem among children. • The horticultural activity program was an effective approach to reduce internet addiction and increase social skills. • A horticultural activity program consisting of six sessions could be implemented to change behavior in children.